(+)-Aeroplysinin-1 Modulates the Redox Balance of Endothelial Cells - García-Vilas García, Javier Alejandro; Martínez-Póveda, Beatriz Amparo; Rodríguez-Quesada, Ana María; Medina-Torres, Miguel Ángel (IOAP-MPDI, 2018)
The bioactive natural compound from marine origin, (+)-aeroplysinin-1, has been shown to exhibit potent anti-inflammatory and anti-angiogenic effects. The aim of the present study was to identify new targets for (+)-aeroplysinin-1 in endothelial cells. The sequential use of 2D-electrophoresis and MALDI-TOF-TOF/MS allowed us to identify several differentially expressed proteins. Four of these proteins were involved in redox processes and were validated by Western blot. The effects of (+)-aeroplysinin-1 were further studied by testing the effects of the treatment with this compound on the activity of several anti- and pro-oxidant enzymes, as well as on transcription factors involved in redox homeostasis. Finally, changes in the levels of total reactive oxygen species and mitochondrial membrane potential induced by endothelial cell treatments with (+)-aeroplysinin-1 were also determined. Taken altogether, these findings show that (+)-aeroplysinin-1 has multiple targets involved in endothelial cell redox regulation.
Keywords: Neovascularización; Aeroplysinin-1; Angiogenesis; Aplysina aerophoba; Endothelial cell; Redox